2003
DOI: 10.1046/j.1365-2656.2003.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating natal dispersal movement rates of female European ducks with multistate modelling

Abstract: Summary 1.We used up to 34 years of capture-recapture data from about 22 100 new releases of day-old female ducklings and multistate modelling to test predictions about the influence of environmental, habitat and management factors on natal dispersal probability of three species of ducks within the Engure Marsh, Latvia. 2. The mean natal dispersal distances were very similar ( c . 0·6-0·7 km) for all three species and were on average 2·7 times greater than breeding dispersal distances recorded within the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Both water cover and river density positively correlated with their abundance. Blums et al (2003) and Skorka et al (2009) demonstrated that rivers and water bodies play important role in landscape scale movements of waterbirds and their use of foraging patches. It is noteworthy that rivers also increase abundance in breeding habitat patches, as shown by Lenda et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Both water cover and river density positively correlated with their abundance. Blums et al (2003) and Skorka et al (2009) demonstrated that rivers and water bodies play important role in landscape scale movements of waterbirds and their use of foraging patches. It is noteworthy that rivers also increase abundance in breeding habitat patches, as shown by Lenda et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, closely-related bird species may show some similarity in dispersal patterns (Delestrade et al, 1996;Negro et al, 1997). Presently, studies have been focused on the factors shaping the bird species to disperse (Stenseth and Lidicker, 1993), including sexbiased (Blums et al, 2003), age-dependent (Pyle, 2001), density-dependent (Cam et al, 2004), body condition (Garant et al, 2005), social status (Baglione et al, 2003), habitat and landscape (Breininger, 1999), food (Coles et al, 2003), parasite (Brown and Brown, 1992) and climate change (Walls et al, 2005).…”
Section: The Main Research Subjects Of Avian Dispersalmentioning
confidence: 99%
“…Animals perceive and react to this structure at many different spatial scales, and each aspect of their biology (e.g. foraging behaviour (Fritz et al 2003), dispersal patterns (Blums et al 2003), animal orientation (Benhamou 1989), and population dynamics (Lewis and Murray 1993) relates to specific sections of this scale. Wiens (1989) called such sections ''domains'' and called the boundaries between them ''transitions''.…”
Section: Introductionmentioning
confidence: 99%